Relationship Between Oropharyngeal Geometry and Vocal Parameters in Subjects With Parkinson's Disease - Paulino, Clarissa Evelyn Bandeira; Silva, Hilton Justino da; Gomes, Adriana de Oliveira Camargo; Silva, Joice Maely Souza da; Cunha, Daniele Andrade da; Coriolano, Maria das Graças Wanderley de Sales; Lopes, Leonardo Wanderley; Lira, Zulina Souza de (Journal of voice, 2024)
To verify whether the dimensions of different segments of the oropharyngeal cavity have different proportions between Parkinson's disease patients and vocally healthy subjects and investigate whether the measurements of these subjects’ oropharyngeal geometry associate with their acoustic measurements of voice. Quantitative, descriptive, cross-sectional, and retrospective study with secondary data, approved by the Human Research Ethics Committee under no. 4.325.029. We used vocal samples and data from the oropharyngeal geometry of 40 subjects – 20 with Parkinson's disease stages I to III and 20 who formed the control group, matched for sex and age. Each group had 10 males and 10 females, mean age of 61 years (±6.0). Formant (F1, F2, and F3) and cepstral measures of the sustained vowel /ε/ were extracted and arranged in the database to determine their values using Praat software. The data were descriptively analyzed, with statistics generated with R software. The proportion of oropharyngeal geometry measurements was arranged by mean values and coefficients of variation. Pearson's linear correlation test was applied to relate voice parameters to oropharyngeal geometry, considering P < 0.05, and linear regression test, to justify F2. The Parkinson's disease group showed a linear relationship between oral cavity length and F1 in males (P = 0.04) and between glottal area and F2 in females (P = 0.00); linear relationships were established according to age in both groups, and a regression model for F2 was estimated (R2 = 0.61). There was no difference between pathological and healthy voices; there was a difference in the proportional relationship of oropharyngeal geometry between the groups. The proportional relationship of oropharyngeal geometry differs between the Parkinson's disease group and the control group, as well as the relationship between oropharyngeal geometry and formant and cepstral values of voice according to the subjects’ sex and age.